Development of Animated Video Learning Media to Improve Students' Understanding of Ablution Procedures - Saepul, Saepul (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
This study aimed to develop and evaluate the effectiveness of animated video learning media to enhance students' understanding of ablution procedures. Utilizing the ADDIE development model, the research was conducted at Public Middle School Palopo with 25 seventh-grade students. Data were collected through interviews, documentation, expert validation, student questionnaires, and performance tests. The development process involved designing and validating the animated video, with a focus on its content, language, and media quality. Validation results indicated high validity scores: 96% for content, 88% for language, and 72% for media design. After revisions, the media was tested for effectiveness, revealing a significant improvement in students' comprehension, with an average performance score of 91.43%. The animated video successfully demonstrated detailed, systematic, and engaging representations of ablution practices, aligning with students' cognitive developmental stages and addressing the limitations of traditional teaching methods. This research emphasizes the possible use of multimedia learning tools to support religious education, particularly for practical topics that require visual demonstrations. Future studies are encouraged to explore broader applications and assess long-term retention of knowledge facilitated by such media.